2022
DOI: 10.1136/rmdopen-2021-001847
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of BNT162b2 mRNA SARS-CoV-2 vaccine in patients with psoriatic arthritis on TNF inhibitors

Abstract: BackgroundScanty data on the immunogenicity of the BNT162b2 vaccine in patients with psoriatic arthritis (PsA) on Tumor Necrosis Factor inhibitors (TNFi) have been published.ObjectiveTo investigate the humoral response to BNT162b2 vaccination patients with PsA on TNFi, comparing immunogenicity with healthy controls.MethodsForty patients with classified PsA on TNFi undergoing vaccination with the BNT162b2 mRNA SARS-CoV-2 vaccine (BioNTech/Pfizer) were enrolled. Fifteen days after the second shot, serum IgG leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…In conclusion, we evidenced a good safety profile of anti-SARS-CoV-2 vaccine in a large cohort of patients affected by IIM. Our findings, which are in line with real-life data coming from patients with other diseases, have found a clinical non-statistically significant risk of relapse in our patients, which occurred seldom, usually mild and in the ones with a more severe and aggressive course of disease: indeed, the only patient who died suffered from a severe, long-standing PM poorly responsive to the treatment Such findings are comparable with the literature data available about other rheumatologic disorders [ 30 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In conclusion, we evidenced a good safety profile of anti-SARS-CoV-2 vaccine in a large cohort of patients affected by IIM. Our findings, which are in line with real-life data coming from patients with other diseases, have found a clinical non-statistically significant risk of relapse in our patients, which occurred seldom, usually mild and in the ones with a more severe and aggressive course of disease: indeed, the only patient who died suffered from a severe, long-standing PM poorly responsive to the treatment Such findings are comparable with the literature data available about other rheumatologic disorders [ 30 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, vaccines seem to be a safe option in rheumatic patients, as large studies, performed in wide cohorts, have not shown any significant risk of relapse in this particular subset of patients [27][28][29][30], even when affected by rare diseases [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…These findings appear to be in line with previous research highlighting an altered immune response against various microbial species and after vaccine administration( 11 ). A similar pattern of response resembles that observed also in other conditions of immunosuppression( 12 ).…”
Section: Discussionsupporting
confidence: 88%
“…For biologics that inhibit certain cytokines (e.g., tumor necrosis factor, interleukin‐6 receptor [IL‐6R], IL‐1R, IL‐17, IL‐12/23, IL‐23), the task force failed to reach consensus on whether or not to temporarily interrupt these following each COVID‐19 vaccine dose. Some panel members felt that withholding treatment for 1–2 weeks was unnecessary, had minimal effect on vaccine response ( 68 , 99 ), and could put the patient at greater increased risk for disease to worsen. In contrast, other task force members felt that even limited evidence suggesting the possibility that these therapies could attenuate vaccine response should result in a recommendation of a temporary interruption of therapy ( 100 , 101 ).…”
Section: Resultsmentioning
confidence: 99%